Efektivitas Perjanjian Kerja Laut Terhadap Keselamatan Kerja Anak Buah Kapal (Abk) - Muhiddin, Nurmiati (Al-Daulah : Jurnal Hukum Pidana dan Ketatanegaraan, 2016)
The employment agreement is the main basis for workers to hold a working relationship, and is the basis for the workers and the workers to demand their rights. When compared, Sea labor agreement with a labor agreement under the Act will be a difference. Sea Labour Agreement are specific, while the agreement is based on the Law of a general nature. Sea Labour Agreement must be made in the presence of government officials who authorized the Harbour Master. In addition, the ship crew and ship operators should be aware of the rights and obligations of each, so as to create a harmonious working relationship between both parties. Ship operators should also pay attention to the well-being of its employees